A Delphi Method Exploration of Performance Pressures and Ethical Leadership Compromises in Business Organizations - Ngcobo, Lloyd Senzo; Reddy, Colin David (Journal of Management and Business Review, 2024)
A deep understanding of the dynamics between performance pressures and ethical leadership becomes crucial in an era of stressful economic recovery. This research explores the complex relationship between organizational performance pressures and ethical leadership, focusing on how these pressures impact ethical decision-making and the challenges of maintaining ethical integrity in demanding environments. Employing a convenience sampling method and the rank-type Delphi method, the study engaged 40 experts from both academic and practical fields to identify and rank key performance pressures that compromise ethical leadership. Significant pressures identified include the imperative to generate positive financial reports, achieve greater efficiency, withstand competitive pressures, and pursue aggressive growth strategies, all eroding ethical leadership. These pressures lead to unethical practices, such as falsifying financial reports, exploiting working conditions, unfair competition, and aggressive merger and acquisition tactics. The findings underscore the critical need for leaders to recognize and manage these pressures effectively to foster an environment conducive to ethical leadership. This study contributes valuable insights into the mechanisms by which performance pressures undermine ethical leadership and highlights the importance of cultivating a culture that promotes normative behavior and addresses ethical challenges, thereby enriching the existing body of knowledge on organizational ethics and leadership.